Relationship Between Nutritional Status and Environmental Factors With Acute Respiratory Infections (ARI) in Toddlers: A Cross-sectional Study - Lusi Agrarina; Andre Utama Saputra; Ranida Arsi; Muhammad Romadhon (School of Health Sciences Al-Ma'arif, 2025)
Acute Respiratory Infection (ARI) is a leading cause of morbidity and mortality among children under five in developing countries, including Indonesia. Poor nutritional status and unhealthy living environments are suspected contributors to the high incidence of ARI. Objective to determine the relationship between nutritional status and environmental factors with the incidence of ARI among toddlers in the working area of Gardu Harapan Public Health Center, Lais District, Musi Banyuasin Regency. This study used a cross-sectional design with a quantitative approach. A total of 105 mothers with children aged 0–59 months were selected using purposive sampling. Data were collected through structured questionnaires and medical records and analyzed using the Chi-Square test. Approximately 60% of children experienced ARI. There was a significant relationship between nutritional status and ARI (p = 0.003), and between environmental factors and ARI (p = 0.003). Children with poor nutritional status and living in unhealthy environments had a higher risk of developing ARI. Nutritional status and environmental conditions are significantly associated with ARI in toddlers. Nutritional interventions and environmental improvements should be conducted simultaneously to reduce ARI incidence.